2005
DOI: 10.1002/bit.20548
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic biodegradation of oleic and palmitic acids: Evidence of mass transfer limitations caused by long chain fatty acid accumulation onto the anaerobic sludge

Abstract: Palmitic acid was the main long chain fatty acids (LCFA) that accumulated onto the anaerobic sludge when oleic acid was fed to an EGSB reactor. The conversion between oleic and palmitic acid was linked to the biological activity. When palmitic acid was fed to an EGSB reactor it represented also the main LCFA that accumulated onto the sludge. The way of palmitic acid accumulation was different in the oleic and in the palmitic acid fed reactors. When oleic acid was fed, the biomass-associated LCFA (83% as palmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
179
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(198 citation statements)
references
References 18 publications
16
179
1
2
Order By: Relevance
“…In this case, the lag phase extended to 400 h, but the process recovered. This phenomenon agrees with Pereira et al (2005) that demonstrated that inhibition by LCFA accumulation was a reversible phenomenon more likely to be related to physical transport limitations, than to metabolic functions.…”
Section: Waste Compositionsupporting
confidence: 92%
“…In this case, the lag phase extended to 400 h, but the process recovered. This phenomenon agrees with Pereira et al (2005) that demonstrated that inhibition by LCFA accumulation was a reversible phenomenon more likely to be related to physical transport limitations, than to metabolic functions.…”
Section: Waste Compositionsupporting
confidence: 92%
“…volatile fatty acid and steroid-like molecules) (Réveillé et al, 2003) (0-28 ppm); (ii) long chain aliphatic carbon (e.g. plant aliphatic biopolymers) (Pereira et al, 2005) and proteins (Dignac et al, 2000) (28-47 ppm); (iii) O-alkyl carbon (e.g. polysaccharides) (Kögel-Knabner, 2002) (47-113 ppm); (iv) aromatic carbon (e.g.…”
Section: Cpmas Nmr Analysismentioning
confidence: 99%
“…During the AD of a co-substrate microorganisms utilize carbon from 25 to 30 times faster than nitrogen [20] and the nitrogen content in WAS compensates a possible lack of nutrients in OFMSW while their content of lipids increases biogas yield [21]. On the other hand a lipid-rich substrate leads to an increase in Long Chain Fatty Acids (LCFAs) which may form a hydrophobic layer that destabilizes the digestion process [22], affecting bacteria transport and reducing contact between the substrate and the encapsulated bacteria. LCFAs entrapment causes the flotation and inhibition of methanogenic bacteria leading to cellular membrane damage [23].…”
Section: Introductionmentioning
confidence: 99%